The biological role and molecular mechanism of transfer RNA-derived small RNAs in tumor metastasis - Dong, Haotian; Ye, Chengyuan; Ye, Xiaohan; Yan, Jianing; Ye, Guoliang; Shao, Yongfu (Frontiers in Oncology, 2025)
Tumor metastasis is a significant contributor to increased cancer mortality. Transfer RNA-derived small RNAs (tsRNAs), a class of endogenous non-coding RNA molecules, play crucial functional roles in various physiological processes, including the regulation of transcription and reverse transcription, the modulation of translation processes, the modification of epigenetic inheritance, the regulation of the cell cycle, etc. Dysregulated tsRNAs are closely related to the occurrence and progression of human malignancies. Accumulating evidence indicates that the abnormal expression of tsRNAs is associated with tumor metastasis through a variety of mechanisms. Hence, we summarize the fundamental structure and biological functions of tsRNAs, with a focus on how tsRNAs influence the tumor metastasis process through downstream targets or the regulation of interactions between upstream and downstream molecules, thereby providing a novel perspective for targeted therapy for tumor metastasis.